Quantitative analysis of the air of some of the public buildings in and near Manhattan - Harris, Lola May (My University, 1905)
Introduction: The discovery of bacteria opened a large and original work. One of attractive field for its most interesting features is that: new and intimate relations are constantly being found between the minute plant life and the health and activities of man and the other animals. The health of mankind depends in a large measure upon the effect-live work or bacteria in disintegrating organic substances which would become a menace and source of disturbance to the normal body processes. These bacteria have been found to be always present in air, water and earth. The object of the experiments here recorded was to determine the relative number of bacteria in the air when quiet and when disturbed, and to gain an idea of the number present in the air of public buildings under the usual conditions. Method: Two tests were made for each building, the material used being agar plates, which were, exposed in different parts of the room or building: A. When the air was quiet and the room unoccupied or but two or three present. This test was usually made in the morning before the room had been occupied or the air disturbed. B. When the air was in motion, due either to the presence of a number of people, or to the commotion caused by sweeping, this test being made, if possible, in the afternoon when the room or, building had seen occupied the greater part of the day. The time of the exposure was determined by preliminary experiments the four minute exposure seeming to give the best results. Preparation of the plates: The Petri dishes, after being boiled twenty minutes, were washed and covered with a cleaning solution for at least twenty minutes, then rinsed with water and allowed to drain until dry. They were next placed in the hot air sterilizer, and kept at 150° C for an hour and: after cooling were partially filled with agar from tubes which had been sterilized on three consecutive days. When the had solidified they were placed in the incubator, for 48, hours and if, at the end of that time,, they were not' contaminated they were ready to be exposed after exposure they were again placed in the incubator, and when 48 hours had expired the colonies were counted. Those in the first group were counted again in 24 hour.
Citation: Harris, Lola May. Quantitative analysis of the air of some of the public buildings in and near Manhattan. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Buildings Tested; Collegte Buildings; Buildings in Manhattan; Theses